2020
DOI: 10.3389/fmicb.2020.560336
|View full text |Cite
|
Sign up to set email alerts
|

Functional Gene Expression in Shark Bay Hypersaline Microbial Mats: Adaptive Responses

Abstract: Microbial mat communities possess extensive taxonomic and functional diversity, which drive high metabolic rates and rapid cycling of major elements. Modern microbial mats occurring in hypersaline environments are considered as analogs to extinct geobiological formations dating back to ∼ 3.5 Gyr ago. Despite efforts to understand the diversity and metabolic potential of hypersaline microbial mats in Shark Bay, Western Australia, there has yet to be molecular analyses at the transcriptional level in these micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…Taxonomic analysis of the microbiota was based on 16S rRNA transcripts, followed by functional and taxonomic annotation of transcripts derived from the mRNA fraction (Campbell et al, 2020). Bushnell, 2018).…”
Section: Metatranscriptomic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Taxonomic analysis of the microbiota was based on 16S rRNA transcripts, followed by functional and taxonomic annotation of transcripts derived from the mRNA fraction (Campbell et al, 2020). Bushnell, 2018).…”
Section: Metatranscriptomic Analysismentioning
confidence: 99%
“…These values were visualized using pheatmap and PCA (ggfortify and ggplot2) in R. Relative abundance of compound groups and isotopic distributions were visualized with scatter or bar plots in OriginPro (Seifert, 2014). Additionally, for downstream functional and biomarker analyses, samples were grouped based off taxonomic similarity (Campbell et al, 2020).…”
Section: Statistical Analysis and Visualizationmentioning
confidence: 99%
“…As stated previously, the Archean Domes microbial system is constantly subject to environmental stress, which could be arguably compared to those experienced by the Shark Bay microbial mats, a recognized terrestrial analog (Wong, White, et al, 2018;Campbell et al, 2020). Therefore, the Archean Domes site is potentially a promising analog for early Earth, and (plausibly) early Mars, just as other potential analogs found in the Cuatro Ciénegas Basin (López-Lozano et al, 2012;Moreno-Letelier et al, 2012;Souza et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…Previous work suggests a tight link between cyanobacterial EPS production and degradation by Bacteroidetes. Earlier studies identified co-enrichments of Bacteroidetes and Cyanobacteria in the same regions of pustular mats (14) and suggested that Bacteroidetes and Alphaproteobacteria most actively produce mRNA transcripts during the day, when Cyanobacteria photosynthesize (68). The extensive functional potential of Bacteroidetes to perform the first steps in degrading fresh cyanobacterial EPS may explain these trends and link Bacteroidetes to other important metabolic guilds in mats.…”
Section: Discussionmentioning
confidence: 99%